Keeping Pace with the Generations! Quantitative Job Insecurity and Retention in Gen Z Workers: The Mediating Roles of Affective Commitment and Psychological Empowerment - Oraibi, Bha-Aldan Mundher; Bawazir, Abdullah Abdulaziz; Emam, Ali Salman Mohammed (International Review of Management and Marketing, 2024)
The workforce is changing as new employees enter the labour pool. Malaysia’s largest demographic segment is currently Gen Z, constituting 38% of the total population, and boasting a monthly disposable income of US$428 million. Over the next ten years, up to 10 million people in Malaysia born after 1995 (i.e., Gen Z) will enter the workforce. The purpose of this research is to investigate the relationship between job security and employee retention through the mediating mechanism of affective organizational commitment and employees’ psychological empowerment among Gen Z, who are currently working and making up part of the workforce in Malaysia. Gen Z is characterized by distinctive attributes, demanding that human resource management (HRM) professionals anticipate potential innovations in their recruitment and training methodologies. Among the paramount concerns confronting HRM lies the challenge of employee retention, which holds a pivotal position in the overall success of an organization. This centrality is underscored by the financial burdens linked to the recruitment and training of fresh personnel, the disruption of business continuity occasioned by employee departures (commonly referred to as ‘turnover’), and the ensuing decline in productivity stemming from employee attrition. One strategy to increase retention is job security, because the finding of this research show that employees who have job security have high commitment and psychological empowerment, as well as high intention to stay in organizations. Implications for theory and research and management practice are discussed.